2023
DOI: 10.2174/1574888x17666220425122317
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Local Injection of Adipose Stem Cells Promotes Ectopic Cartilage Regeneration In Vivo by Modulating Inflammatory Response and Enhancing Cartilage Extracellular Matrix Synthesis in a Porcine Model

Abstract: Background: Uncontrollable inflammatory response following ectopic engineered cartilage implantation is devastating to the aesthetic and functional outcomes of the recipients. Adipose stem cells (ASCs) have a good immunomodulatory capacity via a paracrine mechanism. However, works of literature are scarce regarding ASC modulation in ectopic engineered cartilage regeneration in vivo. This study aims to explore how ASCs modulate the inflammatory response after engineered cartilage implantation and affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 12 Many studies have shown that M2 macrophages exert a chondro-inductive effect on MSCs and promote cartilage regeneration. 18 , 34 , 35 Unsurprisingly, our study revealed that MS-CM can substantially increase the chondrogenic differentiation of MSCs, in which TGF‐β1 is extremely highly expressed. Further functional assays showed that TGF‐β1 is required for mechanically stimulated macrophage-induced promotion of chondrogenic responses of MSCs.…”
Section: Discussionmentioning
confidence: 78%
“… 12 Many studies have shown that M2 macrophages exert a chondro-inductive effect on MSCs and promote cartilage regeneration. 18 , 34 , 35 Unsurprisingly, our study revealed that MS-CM can substantially increase the chondrogenic differentiation of MSCs, in which TGF‐β1 is extremely highly expressed. Further functional assays showed that TGF‐β1 is required for mechanically stimulated macrophage-induced promotion of chondrogenic responses of MSCs.…”
Section: Discussionmentioning
confidence: 78%